2015
DOI: 10.1590/s1984-82502015000400020
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of homoisoflavonoids from Scilla persica HAUSSKN

Abstract: Medicinal plants have many traditional claims including the treatment of ailments of infectious origin. In the evaluation of traditional claims, scientific research is extremely important. In this study, five homoisoflavonoids named 3-(4'-hydroxybenzylidene)-5,7-dihydroxy-6-methoxychroman-4-one(Autumnalin),3-(4'-hydroxybenzyl)-5,7-dihydroxy-6-methoxychroman-4-one (3,9-dihydro-autumnalin), 3-(3',4'-dihydroxybenzyl)-5,8-dihydroxy-7-methoxychroman-4-one,3-(3',4'-dihydroxybenzylidene)-5,8-dihydroxy-7-methoxychroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The MeOH and butanol extracts of the bulbs of Eucomis autumnalis yielded compounds 22 and 30−39, and the EtOH extract of the bulbs of E. bicolor yielded compounds 40 and 41. Compounds 31 and 32 have been isolated previously from both E. autumnalis and E. bicolor, 26 compound 36 from E. autumnalis, 27−29 compounds 30, 40, and 41 from E. bicolor, 27,30,31 compound 33 from E. montana, 32 compound 38 from Muscari armeniacum, 17 compound 39 from Scilla persica, 33 and compound 37 from Ledebouria ovatifolia. 23 Compound 35, 3R-(4′-hydroxybenzyl)-6,8-dihydroxy-5,7dimethoxy-4-chromanone, is a homoisoflavonoid that has not been reported previously with a fully substituted ring A. HRMS showed a protonated molecular ion at m/z 347.11254 corresponding to a molecular formula of C 18 H 18 O 7 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MeOH and butanol extracts of the bulbs of Eucomis autumnalis yielded compounds 22 and 30−39, and the EtOH extract of the bulbs of E. bicolor yielded compounds 40 and 41. Compounds 31 and 32 have been isolated previously from both E. autumnalis and E. bicolor, 26 compound 36 from E. autumnalis, 27−29 compounds 30, 40, and 41 from E. bicolor, 27,30,31 compound 33 from E. montana, 32 compound 38 from Muscari armeniacum, 17 compound 39 from Scilla persica, 33 and compound 37 from Ledebouria ovatifolia. 23 Compound 35, 3R-(4′-hydroxybenzyl)-6,8-dihydroxy-5,7dimethoxy-4-chromanone, is a homoisoflavonoid that has not been reported previously with a fully substituted ring A. HRMS showed a protonated molecular ion at m/z 347.11254 corresponding to a molecular formula of C 18 H 18 O 7 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The MeOH and butanol extracts of the bulbs of Eucomis autumnalis yielded compounds 22 and 30 – 39 , and the EtOH extract of the bulbs of E. bicolor yielded compounds 40 and 41 . Compounds 31 and 32 have been isolated previously from both E. autumnalis and E. bicolor , compound 36 from E. autumnalis , compounds 30 , 40 , and 41 from E. bicolor , ,, compound 33 from E. montana , compound 38 from Muscari armeniacum , compound 39 from Scilla persica , and compound 37 from Ledebouria ovatifolia …”
Section: Resultsmentioning
confidence: 99%
“…These showed low to moderate activity with IC50 values of 74.6 and 30.5 µM for autumnalin and 3,9-dihydro-autumnalin respectively. Additionally, both these compounds showed moderate toxicity against normal human fibroblasts, both with IC50 values of 100 µM (Ebrahimi et al, 2015). Due to the highly toxic effects seen in animals when the plant was ingested, further studies should be done on the isolation of compounds which could potentially show less toxicity in non-tumorigenic models while having significant activity against cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is known as a foodstuff and important plant in traditional medicine for promoting blood circulation, reducing inflammation, as an analgesic [2], and antibacterial agent [3]. Previous studies on Scilla species revealed triterpenoid [4], stilbenoids [5] and cardiac glycosides [6] as well as homoisoflavanones [7][8][9][10][11], which showed antibacterial and anti-angiogenic activities, and inhibited in vitro the growth and sporogenesis of several microorganisms [7,8,11,12].…”
Section: Introductionmentioning
confidence: 99%